DESIGN OF THE INTERPRETIVE SCRIPT OF CATHEDRAL OF TUNJA AS HERITAGE VALUATION STRATEGY - Guzmán Cifuentes, Álvaro Augusto
This article is part of the result of the Interpretive Script designed for the Cathedral of Tunja that responds to its scarce tourist use and the lack of interest in its protection. The script is a tool for touristic guides in Tunja, which allows revealing the meaning of a place, a strategy for valuing the heritage for the community and, at the same time, making visitors’ encounter with the Heritage enjoyable. Consolidate and organize the information available in a structured manner was the most appropriate way to prepare the script, based on qualitative-descriptive methodology and documentary research techniques. The script is the most visible result of the research, in addition to discoveries made along the same as: the location of pieces that are mentioned by different experts and that were understood lost, and the design of a bilingual audio guide. In conclusion, the cathedral is the result of time, representative historic, spiritual, symbolic and artistic manifestation of Colombia, where each of these aspects converge in different evolutionary periods of the Colombian nation.